2011
DOI: 10.1161/circresaha.111.243410
|View full text |Cite
|
Sign up to set email alerts
|

β-Myosin Heavy Chain Is Induced by Pressure Overload in a Minor Subpopulation of Smaller Mouse Cardiac Myocytes

Abstract: Rationale Induction of the fetal hypertrophic marker gene beta-myosin heavy chain (β-MyHC) is a signature feature of pressure overload hypertrophy in rodents. β-MyHC is assumed present in all or most enlarged myocytes. Objective To quantify the number and size of myocytes expressing endogenous β-MyHC using a flow cytometry approach. Methods and Results Myocytes were isolated from the LV of male C57Bl/6J mice after transverse aortic constriction (TAC), and the fraction of cells expressing endogenous β-MyHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
67
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 59 publications
9
67
0
2
Order By: Relevance
“…However, recent studies have shown an unexpected heterogeneity of regulated expression of Myh7 (569,570), and this needs to be taken into account when assessing effects of T 3 .…”
Section: And Recommendation 52amentioning
confidence: 99%
“…However, recent studies have shown an unexpected heterogeneity of regulated expression of Myh7 (569,570), and this needs to be taken into account when assessing effects of T 3 .…”
Section: And Recommendation 52amentioning
confidence: 99%
“…This experiment was also important considering that pathologic hypertrophy is often indicated by an upregulation of the ␤-MHC isoform (30). As shown in Fig.…”
Section: Effect Of A57g On Mhc Isoform Expression and Myofilament Promentioning
confidence: 99%
“…The effect of isoproterenol on expression of ␤-MHC in AKAP5 ϩ/ϩ NMVCM versus AKAP5 Ϫ/Ϫ NMVCM was determined by immunohistochemistry. For this purpose, we used a validated highly specific antibody to ␤-MHC (33). As shown in Fig.…”
Section: Cardiomyocytes From Akap5mentioning
confidence: 99%